A decrease in cluster of differentiation 2 expression on natural killer cells is associated with polycystic ovary syndrome but not influenced by metformin in a mouse model - Czika, Armin; Yang, Yin; Yang, Jun-Pu; Adu-Gyamfi, Enoch Appiah; Ullah, Amin; Ruan, Ling-Ling; Chen, Xue-Mei; Wang, Ying-Xiong; Wang, Mei-Jiao; Ding, Yu-Bin (Biology of reproduction, 2022)
Problem: Natural killer (NK) cells from the peripheral blood and spleen represent the source from which various tissues replenish their immune cell populations. Hyperandrogenism and high interleukin-2 (IL-2) levels are factors present in polycystic ovary syndrome (PCOS). These factors and metformin, one of the commonest medications used in treating PCOS, may have an impact on NK cells. However, this is presently unknown. Here, we aimed to assess the distribution of peripheral blood and splenic NK cells and their CD2 and CD94 expression patterns in a PCOS mouse model and test whether metformin could reverse these effects. Method of study: Four mouse groups were designed as follows (n = 15/group): control, PCOS, PCOS plus vehicle, PCOS plus metformin. Dehydroepiandrosterone and a high-fat diet were administered to induce the PCOS mouse model. Flow cytometry was used to analyze the expressions of CD2 and CD94 on peripheral blood and splenic NK cells. Results: PCOS mice had a low surface-density of CD2 on peripheral blood NK cells and a decreased percentage of CD2+ splenic NK cells. Metformin administration did not significantly influence these changes; however, it reduced the splenic NK cell counts. Conclusions: Our findings proved the association of PCOS with an altered expression of CD2 on peripheral blood and splenic NK cells and that of metformin with a lowered splenic NK cell reserve in PCOS conditions. These findings could further unlock key mechanisms in PCOS pathophysiology and in the mechanism of action of metformin, towards improving PCOS management. Summary Sentence A decreased density of CD2 receptor expression on peripheral blood NK cells and a decreased percentage of CD2+ splenic NK cells were associated with PCOS but not influenced by metformin administration in a DHEA-induced PCOS mouse model. Graphical Abstract